Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Differential Effects of Legume Species on the Recovery of Soil Microbial Communities, and Carbon and Nitrogen Contents, in Abandoned Fields of the Loess Plateau, China - Jin Hua Li; Shu Mei Jiao; Rong Qing Gao; Richard D. Bardgett (Environmental Management, 2012)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

Induction of Chlamydospore Formation in Fusarium by Cyclic Lipopeptide Antibiotics from Bacillus subtilis C2 - Lei Li; MingChuan Ma; Rong Huang; Qing Qu; GuoHong Li; JinWei Zhou; KeQin Zhang; KaiPing Lu; XueMei Niu; Jun Luo (Journal of Chemical Ecology, 2012)

An antifungal compound from Trichoderma harzianum SQR-T037 effectively controls Fusarium wilt of cucumber in continuously cropped soil - Li-Hua Chen; Ya-Qing Cui; Xing-Ming Yang; Di-Kun Zhao; Qi-Rong Shen (Australasian Plant Pathology, 2012)

The expression level of Rosa Terminal Flower 1 (RTFL1) is related with recurrent flowering in roses - Li-Na Wang; Yun-Feng Liu; Yu-Man Zhang; Rong-Xiang Fang; Qing-Lin Liu (Molecular Biology Reports, 2012)

High level interleukin-6 in the medium of human pancreatic cancer cell culture suppresses production of neurotransmitters by PC12 cell line - Rong Li; Jian Hou; Qing Xu; Qing-Jun Liu; Yi-Jun Shen; Gary Rodin; Madeline Li (Metabolic Brain Disease, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)